Comparison of sitting positions on a pressure sensing mat over time - Srinivasan Niranjan; Mojabi Seyedehmina; Adeel Altaf Muhammad; Babur Alparslan; Skerl Katrin (Current Directions in Biomedical Engineering)
These days, many jobs like working in an office include sitting in chairs for a long time which could lead to work-related disorders such as musculoskeletal issues. Inappropriate postures can cause muscle fatigue in certain regions, resulting in pain and discomfort. Analysis of different types of postures to indicate discomfort could help us choose an optimal posture. This study evaluates five different sitting postures in an office chair for comfort and discomfort. Each posture was held for 18 minutes with a two minute break between postures. Six participants with an equal number of male and female subjects were chosen. The sitting posture correlates with the distribution of the weight on the seat, which can be measured by pressure sensors. The pressure distribution was obtained using a custom-built pressure mat and the maximum pressure were evaluated. The McGill Questionnaire construct was used to find subjective discomfort at each minute. There was no difference in results for both sexes. Overall, leaning to one side was felt more comfortable while sitting with a curved back caused the highest discomfort.